Temporal dynamics of ovine airway epithelial cell differentiation at an air-liquid interface - O’Boyle, Nicky; Sutherland, Erin; Berry, Catherine C.; Davies, Robert L. (PloS one, 2017)
The respiratory tract and lungs are subject to diverse pathologies with wide-ranging implications for both human and animal welfare. The development and detailed characterization of cell culture models for studying such forms of disease is of critical importance. In recent years the use of air-liquid interface (ALI)-cultured airway epithelial cells has increased markedly, as this method of culture results in the formation of a highly representative, organotypic in vitro model system. In this study we have expanded on previous knowledge of differentiated ovine tracheal epithelial cells by analysing the progression of differentiation over an extensive time course at an ALI. We observed a pseudo-stratified epithelium with ciliation and a concurrent increase in cell layer thickness from 9 days post-ALI with ciliation approaching a maximum level at day 24. A similar pattern was observed with respect to mucus production with intensely stained PAS-positive cells appearing at day 12. Ultrastructural analysis by SEM confirmed the presence of both ciliated cells and mucus globules on the epithelial surface within this time-frame. Trans-epithelial electrical resistance (TEER) peaked at 1049 Ω × cm2 as the cell layer became confluent, followed by a subsequent reduction as differentiation proceeded and stabilization at ~200 Ω × cm2. Importantly, little deterioration or de-differentiation was observed over the 45 day time-course indicating that the model is suitable for long-term experiments.